Los "partidos pequeños" en el espacio público mediático y la falta de pluralidade: las elecciones legislativas de 2011 en Portugal - Morais, Ricardo (2014)
The decision of the Tribunal of Oeiras to force broadcasters to hold public debates between political parties was an event that defined the electoral campaign for the legislative elections held on June 5, 2011 in Portugal. The starting point is the decision to take up the issue that acquired new relevance with this ruling: the media treatment of the candidates in the electoral campaigns. The news coverage given by the print media to the "small parties" after the Tribunal decision is analyzed. We begin with the hypothesis that after the ruling, the print media altered their coverage of the parties with no parliamentary seats.